2013
DOI: 10.1126/scitranslmed.3006406
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Leishmania Hemoglobin Receptor–Encoding DNA Protects Against Visceral Leishmaniasis

Abstract: Leishmaniasis is a severe infectious disease. Drugs used for leishmaniasis are very toxic, and no vaccine is available. We found that the hemoglobin receptor (HbR) of Leishmania was conserved across various strains of Leishmania, and anti-HbR antibody could be detected in kala-azar patients' sera. Our results showed that immunization with HbR-DNA induces complete protection against virulent Leishmania donovani infection in both BALB/c mice and hamsters. Moreover, HbR-DNA immunization stimulated the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…Recently, we have shown that Ldgp63 is trafficked via Rab1 dependent conventional secretory pathway in Leishmania (36). Moreover, we have also shown that Leishmania has conserved trafficking pathways like higher eukaryotic cells (37)(38)(39)(40)(41)(42)(43)(44). Thus, it is tempting to speculate that Ldgp63 might exit from ER by Sar1-dependent COPII mediated process.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that Ldgp63 is trafficked via Rab1 dependent conventional secretory pathway in Leishmania (36). Moreover, we have also shown that Leishmania has conserved trafficking pathways like higher eukaryotic cells (37)(38)(39)(40)(41)(42)(43)(44). Thus, it is tempting to speculate that Ldgp63 might exit from ER by Sar1-dependent COPII mediated process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, depletion, overexpression, or generation of the null-mutant of target gene/protein shows the phenotype and affects the viability of the cells and thereby indicates the essential functions of the respective Rabs in an organism. Previously, we have shown that Hb endocytosis is a clathrin-mediated process in Leishmania (23)(24)(25) and is essential for parasite survival (40). Therefore, we have used Hb as a receptor-mediated endocytic probe and ϩ/Ϫ , and Leishmania:Rab5b ϩ/Ϫ .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, protective immunity against these obligatory intracellular parasites requires T-helper 1 (Th1 type) cellular immune responses, including interferon (IFN)-γ-secreting CD4 T cells and cytotoxic CD8 T cells [1,3]. To blunt the generation of protective immunity, leishmania parasites use immune-avoidance mechanisms, including changes in interleukin (IL)-10 expression [4].…”
Section: Introductionmentioning
confidence: 99%